Epithelioid angiosarcoma arising in schwannoma: Report of three Chinese cases with review of the literature - Li, Chao; Chen, Ying; Zhang, Hong; Zheng, Xiongwei; Wang, Jian (Pathology international, 2012)
Angiosarcoma arising in a schwannoma is extremely rare with only eleven cases having been reported in the English literature. We describe here three further cases occurring in adult males with a pre‐existing longstanding schwannoma. The tumor arose each from the vagus, ischiadic and adrenergic nerve respectively. None of the patients had von Recklinghausen's disease. Microscopically, the tumor was composed of a mixture of a benign schwannoma and an epithelioid angiosarcoma. The two components changed abruptly within the tumor. The endothelial cell differentiation was confirmed by immunohistochemistry. A review of published reports, including the present cases, suggests a poor prognosis with a high rate of local recurrence, distant metastasis and mortality.